Potensi Minyak Atsiri Bunga Lawang (Illicium verum) sebagai Repelen Nyamuk Aedes aegypti - Eva Lestari; Bondan Fajar Wahyudi; Adil Ustiawan; Dian Indra Dewi (BALABA: JURNAL LITBANG PENGENDALIAN PENYAKIT BERSUMBER BINATANG BANJARNEGARA, 2019)
Dengue Hemorrhagic Fever (DHF) is still a become public health problem in the world. In 2017, there were 68,407 cases with 493 deaths DHF cases in Indonesia . The incidence rate of DHF in 2017 was 26,10/100,000 population. DHF was caused by dengue virus which was transmitted through the bites of Aedes aegypti. Several types of plants such as stems, leaves, and flowers can be used as natural ingredients for repelling Ae. aegypti, Star anise (Illicium verum) has a chemical compound that can be used as a mosquito repellent. The purpose of this study was to know the potential of star anise essential oil as repellents of Ae. aegypti. This study was an experimental study with post test only with control group design. The experiment to test the repellency of star anise essential oil was carried out using concentrations of 10%, 20%, 30%, 40%, and 50% on 3-5 days old female Ae. aegypti. The result of this study showed that repellency index of star anise essential oil at concentration 10%, 20%, 30%, 40% and 50% during 6 hours were 58.1%; 63.51%; 59.95%; 49.45% and 65.32%. Star anise essential oil at concentration 10%, 20%, 30%, 40%, and 50% can provide protection against the bites of Ae. aegypti for 1 until 2 hours.